Narrative review of current neuromodulation modalities for spinal cord injury - Medina, Roi; Ho, Alison; Reddy, Rajiv; Chen, Jeffrey; Castellanos, Joel (Frontiers in Pain Research, 2023)
Neuromodulation is a developing field of medicine that includes a vast array of minimally invasive and non-invasive therapies including transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS), and spinal cord stimulation (SCS). Although the current literature surrounding the use of neuromodulation in managing chronic pain is abundant, there is an insufficient amount of evidence specifically regarding neuromodulation in patients with spinal cord injury (SCI). Given the pain and functional deficits that these patients face, that are not amenable to other forms conservative therapy, the purpose of this narrative review is to examine and assess the use of various neuromodulation modalities to manage pain and restore function in the SCI population. Currently, high-frequency spinal cord stimulation (HF-SCS) and burst spinal cord stimulation (B-SCS) have been shown to have the most promising effect in improving pain intensity and frequency. Additionally, dorsal root ganglion stimulation (DRG-S) and TMS have been shown to effectively increase motor responses and improve limb strength. Although these modalities carry the potential to enhance overall functionality and improve a patient’s degree of disability, there is a lack of long-term, randomized-controlled trials in the current space. Additional research is warranted to further support the clinical use of these emerging modalities to provide improved pain management, increased level of function, and ultimately an overall better quality of life in the SCI population.